Interlibrary Book Delivery Service to Home (DOLAR Service) at the Kediri Public Library - Andini Rismiawati; Aam Mariyamah (Alexandria: Journal of Library and Information Science, 2024)
Delivery Book Layanan Antar Pustaka ke Rumah or Delivery Book Service between Libraries to Home (DOLAR service) is an innovation of the circulation service held by the Kediri Public Library for users. This study aims to analyse the DOLAR services held by the Kediri Public Library. Data was collected through interviews with users who have used the DOLAR services and librarians related to the DOLAR service as well as direct observation of the DOLAR service process at the Kediri Public Library. The results of the study show that theDOLAR service is quite good in the context of its service. It can be said to be good because so far users can access landing in the DOLAR service easily and quickly. The frequency of borrowing is quite a lot in the period of time per month. So that the DOLAR service is very helpful for the needs of information sources and references needed by users without having to borrow directly from the library.